The structure and mechanical properties of articular cartilage are highly resilient towards transient dehydration. (1st January 2016) - Boettcher, K.; Kienle, S.; Nachtsheim, J.; Burgkart, R.; Hugel, T.; Lieleg, O.
Graphical abstract: Abstract: Articular cartilage is a mechanically highly challenged material with very limited regenerative ability. In contrast to elastic cartilage, articular cartilage is exposed to recurring partial dehydration owing to ongoing compression but maintains its functionality over decades. To extend our current understanding of the material properties of articular cartilage, specifically the interaction between the fluid and solid phase, we here analyze the reversibility of tissue dehydration. We perform an artificial dehydration that extends beyond naturally occurring levels and quantify material recovery as a function of the ionic strength of the rehydration buffer. Mechanical (indentation, compression, shear, and friction) measurements are used to evaluate the influence of de- and rehydration on the viscoelastic properties of cartilage. The structure and composition of native and de/rehydrated cartilage are analyzed using histology, scanning electron microscopy, and atomic force microscopy along with a 1, 9-dimethylmethylene blue (DMMB) assay. A broad range of mechanical and structural properties of cartilage can be restored after de- and rehydration provided that a physiological salt solution is used for rehydration. We detect only minor alterations in the microarchitecture of rehydrated cartilage in the superficial zone and find that these alterations do not interfere with the viscoelastic and tribological properties of the tissue. Statement of Significance: We here demonstrate the sturdiness of articular cartilage towards changes in fluid content and show that articular cartilage recovers a broad range of its material properties after dehydration. We analyze the reversibility of tissue dehydration to extend our current understanding of how the material properties of cartilage are established, focusing on the interaction between the fluid and solid phase. Our findings suggest that the high resilience of the tissue minimizes the risk of irreversible material failure and thus compensates, at least in part, its poor regenerative abilities. Tissue engineering approaches should thus not only reproduce the correct tissue mechanics but also its pronounced sturdiness to guarantee a similar longevity.